Taphonomy in Archaeology: With Special Emphasis on Man as a Biasing Factor - Noe-Nygaard, Nanna (Journal of Danish Archaeology, 1987)
Taphonomy in Archaeology: With Special Emphasis on Man as a Biasing Factor